Model Kinetika Ekstraksi Minyak Atsiri Sereh Dapur (Cymbopogon citratus) Metode Distilasi Uap Air-Kohobasi - Safira Kanza; Rosatul Jennah; Sugiyanto Saiin (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The essential oil of lemongrass (Cymbopogon citratus) is a high-value commodity widely used in the food, pharmaceutical, and cosmetic industries due to its bioactive components such as citral. Optimizing its distillation process is necessary to achieve maximum yield with time and energy efficiency. This study aims to determine the hourly yield distribution of essential oil from Lombong-type lemongrass during steam distillation and to analyze its extraction kinetics to identify the optimal distillation duration. Distillation was conducted for four hours with yield recorded each hour, and the data were analyzed using pseudo-first-order and pseudo-second-order kinetic models. The results showed that the highest yield was obtained in the first hour (0.1882%), followed by a sharp decline, with no additional yield observed in the fourth hour. The pseudo-first-order model showed the best fit to the experimental data with a rate constant of k = 0,8012/hour. Meanwhile the pseudo-second-order model did not fit well. These findings indicate that the extraction process is dominated by external diffusion and the rapid release of surface volatile compounds. Therefore, it is recommended that distillation duration be limited to two hours to optimize energy and time efficiency.